Factors Influencing the Behavior of Implementing 3M Plus in Efforts to Prevent Dengue Hemorrhagic Fever (DHF) in the Working Area of the Kenali Besar Community Health Center in Jambi City in 2025 - Lola Fatimah Menrofa; Adila Solida; Fajrina Hidayati; Rd. Halim; Oka Lesmana S (International Journal of Health Engineering and Technology, 2026)
Dengue Hemorrhagic Fever (DHF) is still one of the public health problems in Jambi City, especially in the working area of ​​Kenali Besar Community Health Center which shows an increase in cases every year, with a larvae-free rate of 84%, still below the national target of ≥95%. Prevention efforts can be done through the implementation of 3M Plus behavior, but its implementation in the community is still not optimal. The purpose of this study was to determine the factors that influence the behavior of implementing 3M Plus in efforts to prevent Dengue Hemorrhagic Fever (DHF) in the working area of ​​Kenali Besar Community Health Center, Jambi City in 2025. This study used a quantitative method with a Cross Sectional design. The population in this study were people living in the working area of ​​Kenali Besar Community Health Center. The research sample consisted of 95 respondents selected using a multistage sampling technique. Data were collected using a questionnaire and analyzed using the Chi-Square test. The majority of respondents were in the 45-54 year age group (37.9%) and the majority of respondents were female (77.9%). The results of the study showed a significant relationship between knowledge (p-value = 0.01) and attitude (p-value = 0.00) with the behavior of implementing 3M Plus. Meanwhile, the availability of facilities and infrastructure (p-value = 0.60) and the role of health workers (p-value = 0.91) did not show a significant relationship. The better the community's knowledge and attitude, the greater the likelihood they will implement 3M Plus behavior in preventing dengue fever. It is hoped that health workers can improve education, assistance, and community empowerment to strengthen the implementation of 3M Plus in a sustainable manner.